Robotic transabdominal preperitoneal repair for bilateral obturator hernia: a video vignette - Sungwoo Jung; Hyung Soon Lee (Journal of Minimally Invasive Surgery)
Obturator hernias (OHs) are a rare cause of bowel obstruction that requires immediate surgical intervention to prevent morbidity and mortality. Patients with OHs present with acute intestinal obstruction secondary to incarceration, with a high morbidity and mortality rate due to delayed diagnosis and treatment. Although several surgical approaches have been reported, a standard approach for OH treatment has not yet been established. Here, we report the case of a 74-year-old woman who presented with bilateral OHs. The patient presented at our institution with pain in the left lower quadrant. Computed tomography revealed preperitoneal fat in both obturator foramen. Robotic transabdominal preperitoneal (R-TAPP) bilateral OH repair was performed, and a mesh was placed over both obturator foramen. The patient recovered without postoperative complications and was discharged on postoperative day 2. This suggests that the R-TAPP approach is safe for OH repair without incarceration.